Enhancing Electron Correlation at a 3d Ferromagnetic Surface. Issue 3 (18th November 2022) - Janas, David Maximilian; Droghetti, Andrea; Ponzoni, Stefano; Cojocariu, Iulia; Jugovac, Matteo; Feyer, Vitaliy; Radonjić, Miloš M.; Rungger, Ivan; Chioncel, Liviu; Zamborlini, Giovanni; Cinchetti, Mirko
Abstract: Spin‐resolved momentum microscopy and theoretical calculations are combined beyond the one‐electron approximation to unveil the spin‐dependent electronic structure of the interface formed between iron (Fe) and an ordered oxygen (O) atomic layer, and an adsorbate‐induced enhancement of electronic correlations is found. It is demonstrated that this enhancement is responsible for a drastic narrowing of the Fe d‐bands close to the Fermi energy ( E F ) and a reduction of the exchange splitting, which is not accounted for in the Stoner picture of ferromagnetism. In addition, correlation leads to a significant spin‐dependent broadening of the electronic bands at higher binding energies and their merging with satellite features, which are manifestations of a pure many‐electron behavior. Overall, adatom adsorption can be used to vary the material parameters of transition metal surfaces to access different intermediate electronic correlated regimes, which will otherwise not be accessible. The results show that the concepts developed to understand the physics and chemistry of adsorbate–metal interfaces, relevant for a variety of research areas, from spintronics to catalysis, need to be reconsidered with many‐particle effects being of utmost importance. These may affect chemisorption energy, spin transport, magnetic order, and even play a key role in the emergence of ferromagnetism at interfaces between non‐magnetic systems. Abstract : Does adatom adsorption on the surface of a 3D ferromagnet influence electron correlation? A far from trivial question! Using state‐of‐the‐art theoretical and experimental methods, it is found that an iron surface in contact with oxygen represents a moderately correlated system with some features in between metallic Fe and the Mott insulator FeO.